Robert multiplicou (–2ab2) por (–5a2b2) e do resultado subtraiu (–3a3b4). O resultado obtido foi:
a) 13a3b4
b) 7a3b4
c) –13a3b4
d) –3a6b8
e) 7a6b8
obrigada pessoal
Respostas
respondido por:
12
(-2ab²).(-5a²b²)=x
10a³b^4=x
x-(-3a³b^4)=y
10a³b^4+3a³b^4=y
13a³b^4=y
letra a
10a³b^4=x
x-(-3a³b^4)=y
10a³b^4+3a³b^4=y
13a³b^4=y
letra a
respondido por:
2
= [(–2ab²) . (–5a²b²) ] - (–3a³b⁴).
= [ - 2.(-5).a.a².b².b²] + 3a³b⁴
= [ 10a³b⁴] + 3a³b⁴
= 13a³b⁴
Resp.: a) 13a³b⁴
= [ - 2.(-5).a.a².b².b²] + 3a³b⁴
= [ 10a³b⁴] + 3a³b⁴
= 13a³b⁴
Resp.: a) 13a³b⁴
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás